Edukasi Tentang Pentingnya Mengenal Gangguan Kesehatan Mental Pada Remaja di SMA Bawakaraeng - Yantimala Mahmud; Basmalah Harun; Sanghati Sanghati; Heldy Yati Bouty; Reski Ramdani (Universitas Muhammadiyah Manado, 2020)
Adolescence is a challenging period because it involves the transition from childhood to adulthood. Physical and psychological changes in adolescents can have an impact on their mental health. To prevent mental disorders in teenagers, various prevention efforts continue to be carried out, including providing education about mental health in teenagers, but at Bawakaraeng High School they have never received education about the importance of recognizing mental disorders in teenagers. The aim of this community service is to provide mental health information including efforts to prevent mental disorders in teenagers with thought stopping and five finger hypnosis. Community service was carried out at Bawakaraeng High School, November 16 2020 with a total of 60 students participating. The results of this service activity showed an increase in knowledge about mental health in adolescents, namely from 16,67% to 83,33% in the good category and participants were able to carry out stress management with mental health and five finger hypnosis.. Adolescent mental health education can provide increased knowledge about adolescent mental health and stress management that can be carried out by adolescents.